Method of luminescent analysis of the state of photosynthetic apparatus of plants; IOP Conference Series: Materials Science and Engineering; Vol. 754 : High Technology: Research and Applications (HTRA-2019) - Bylkov D. V. (2020, 2020)
Title screen